2019
DOI: 10.21815/jde.019.033
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence as a Predictor of Dental Hygiene Clinical Teaching Effectiveness

Abstract: The development of strong interpersonal relationships between clinical instructors and students has been found to contribute to clinical teaching efectiveness (CTE). In addition, strong interpersonal relationships are more likely to occur in individuals who possess a high level of emotional intelligence (EI). However, an examination of the impact of a clinical instructor's EI on CTE has not been extensively investigated. The aims of this study were to measure the CTE and EI of dental hygiene clinical instructo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…15 Developing techniques to improve EI among dental and dental hygiene students remain critical due to the existing literature demonstrating the implications of EI with student success in didactic and clinical environments, 14 the ethical decision making process, 16 and the interactions between clinical instructors and students. 17 The findings in our study found most of the professionalism domain scores were in the moderate range except for agreeableness and conscientiousness, which were in the high range. These professionalism domain scores seem consistent with the domain scores of dental students who were rated by calibrated faculty members.…”
Section: Discussionsupporting
confidence: 48%
“…15 Developing techniques to improve EI among dental and dental hygiene students remain critical due to the existing literature demonstrating the implications of EI with student success in didactic and clinical environments, 14 the ethical decision making process, 16 and the interactions between clinical instructors and students. 17 The findings in our study found most of the professionalism domain scores were in the moderate range except for agreeableness and conscientiousness, which were in the high range. These professionalism domain scores seem consistent with the domain scores of dental students who were rated by calibrated faculty members.…”
Section: Discussionsupporting
confidence: 48%
“…The dynamic of clinical instruction may be affected by the EI scores of the clinical faculty. Dental hygiene instructors with higher EI scores demonstrated higher levels of teaching effectiveness than dental hygiene instructors with lower EI scores 18 . The EI scores of the dental student and clinical faculty may impact the quality of the teaching and learning relationship.…”
Section: Discussionmentioning
confidence: 94%
“…Prior to our study, minimal research had been conducted to explore the attributes of effective clinical instructors in dental hygiene education 3,18,19 . Our findings identified attributes in dental hygiene clinical instructors that may contribute to effective teaching.…”
Section: Discussionmentioning
confidence: 97%
“…Researchers in many health professions (nursing, medicine, physical therapy, dentistry) have sought to identify characteristics of effective clinical instructors and have used this information to create tools to measure clinical teaching effectiveness (CTE) in their disciplines 2,4‐17 . However, in dental hygiene education, only a few studies have explored the attributes of an effective clinical instructor 3,18,19 . The aim of this study was to identify the attributes of dental hygiene clinical instructors associated with effective teaching.…”
mentioning
confidence: 99%